2003
DOI: 10.1021/es026153z
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Transport of 17β-Estradiol in Soil−Water Systems

Abstract: Over the past several years, there has been an increase in concern regarding reproductive hormones in the environment To date, there exists limited research on the fate and transport of these chemicals in the environment. In this study, a series of laboratory batch sorption and miscible-displacement experiments were done using radiolabeled [14C]17beta-estradiol. The 17beta-estradiol concentrations that were used were similar to those found in manures that are applied to field soils. Equilibrium batch experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
167
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(193 citation statements)
references
References 18 publications
20
167
6
Order By: Relevance
“…Testosterone binds strongly to the organic phase of soil particles and seems more mobile in soils (Lee et al, 2003;Finlay-Moore et al, 2000;Casey et al, 2003Casey et al, , 2004Stumpe and Marschner, 2007) and is less resistant against microbial degradation (Stumpe and Marschner, 2007;Horinouchi et al, 2001); the degradation pathway and persistence in natural soils are poorly understood (Fan et al, 2007;Stumpe and Marschner, 2007). Although it was found that testosterone degraded rapidly, it appeared to have a greater potential to migrate to depths in the soil where biodegradation rates are reduced (Finlay-Moore et al, 2000) than the potential for subsurface water contamination to increase.…”
Section: Article In Pressmentioning
confidence: 99%
“…Testosterone binds strongly to the organic phase of soil particles and seems more mobile in soils (Lee et al, 2003;Finlay-Moore et al, 2000;Casey et al, 2003Casey et al, , 2004Stumpe and Marschner, 2007) and is less resistant against microbial degradation (Stumpe and Marschner, 2007;Horinouchi et al, 2001); the degradation pathway and persistence in natural soils are poorly understood (Fan et al, 2007;Stumpe and Marschner, 2007). Although it was found that testosterone degraded rapidly, it appeared to have a greater potential to migrate to depths in the soil where biodegradation rates are reduced (Finlay-Moore et al, 2000) than the potential for subsurface water contamination to increase.…”
Section: Article In Pressmentioning
confidence: 99%
“…For example, the sorption of oestradiol-17 is associated with the surface area and/or the cation exchange capacity of the soil, with high correlation to particle size (clay) and organic matter. K F values for this substance were in the range of 86-6670 l kg −1 , with K om values of 1800-72500 l kg −1 (median 2600 l kg −1 ) (Casey et al, 2003). In soil column leaching studies performed with oestradiol-17 , K om values ranging from 950 to 1700 l kg −1 were determined.…”
Section: Functional Validation For Surface Watermentioning
confidence: 92%
“…3), which suggests that they had higher mobility in greenhouse soil. In particular, TS is more mobile in soil than estrogen and is more likely to be leached from the soil and reach the groundwater (Casey et al, 2003;Lee et al, 2003). Estrogens and androgens have been found in groundwater samples adjacent to operating swine and beef cattle facilities in previous studies (Arnon et al, 2008;Bartelt-Hunt et al, 2011).…”
Section: Tablementioning
confidence: 94%